A Multiuser Shared Virtual Environment for Facility Management. (2016) - Shi, Yangming; Du, Jing; Lavy, Sarel; Zhao, Dong
Abstract: Facility management (FM) is a critical component of building sustainability because a late response to the FM needs will add unnecessary wastes. A lack of communication has been criticized as an impediment to improving the common understanding of FM requirements among the stakeholders and in turn affects the efficiency of FM. Recent developments in Virtual Reality (VR) have encouraged the utilization of interactive building visualization in the design, construction, and maintenance of different types of facilities. This study finds the interpersonal interaction in the VR environment to be a critical factor in the effective communication in FM by creating a shared immersive experience. To prove the concept, a Building Information Modelling (BIM)-based VR environment tool was developed to bring remotely located stakeholders – building occupants, facility managers, vendors and designers – together to walk through in the same virtual building. It enables real-time interactions of remote stakeholders in the same environment, with a shared immersive walkthrough experience. This tool offers an alternative communication method for sustainable FM. Unity 3D was used to create the interactive environment, and Photon Unity Networking (PUN) was used to implement the cross-platform multiuser function. A case study has shown that this alternative communication method can help stakeholders examine the same facility in remote locations and improve the efficiency of communication.